(untitled) (Revista Brasileira Multidisciplinar, 2022)
Hospitals are responsible for health care for patients with acute and/or chronic illnesses, which have the potential for clinical instability and complications of their health condition. In this context, this article aimed to make a theoretical reference on the management of supplies in the hospital pharmacy and, in addition to presenting the conceptual aspects, recommendations were discussed in terms of carrying out these services in facing the current pandemic. To this end, a narrative review was carried out that included the recruitment of information through consultations: in scientific articles from the electronic library, in specific legislation and in specialized books in the area. All stages of drug logistics, selection, programming, acquisition, storage and distribution are fundamental and need to have their roles valued and rediscussed according to the current context. Access to medicines is an essential condition for rational use, as well as for the resolution and efficiency of hospital care, requiring from the administrators of this segment greater investments on pharmaceutical services to face the Coronavirus Disease pandemic-19 (COVID-19).